The Crown and the Cage: Female Identity in Dickinson’s ‘Title Divine—is mine!’ (1072) and ‘She rose to His Requirement— dropped’ (732) - Aryal, Kamana; Panthee, Dinesh (Kalika Journal of Multidisciplinary Research, 2025)
This paper seeks to explore the bleak condition of women’s lives during the Victorian period, drawing connections to the poet’s personal trauma as reflected in Emily Dickinson’s poems “Title Divine—is mine!” (1072), and “She rose to His Requirement—Dropped” (732), from the Collected Poems of Emily Dickinson. These poems seem to be connected to Dickinson’s life from her child days to adulthood expressing the hints regarding her death. This article aims to advocate the incarcerated life of Victorian women sinking into the solemn experiences of the poet. Her persona’s melancholy represents the Victorian era’s subjugation towards women. The apparent evidences in the poetic lines placidly speaks how Dickinson was immured in patriarchal domain; how her wings were burnt making her fearful toward marriage and imagines herself to be expected to be divine to adore her husband’s flaws and sate his demands by self-sabotaging but that is ever overlooked. Applying a feminist perspective strongly supports the article’s main argument, particularly through references to the poet’s own autobiographical experiences. The inclusion of Mary Wollstonecraft’s A Vindication of the Rights of Woman, alongside contributions from notable feminists before and after the Victorian era, adds depth to the analysis of the traumatic realities faced by women during that time.